Der Filmkomponist Max Steiner (1888-1971) - Wegele, Peter (2012)
This is the first monograph about the Austro-American Composer Max Steiner (1888-1971), one of the great pioneers of film music in the so-called Golden Age of Hollywood. In the early 1930ies with his visionary energy he helped to establish symphonic film music as an integrated part in the film production process. In contrary to many of his colleagues, Mr. Steiner had devoted himself completely to film music. Therefore the preoccupation with Max Steiner's music gives a very valuable insight into the craft of film composing. Supported by many quotes and music examples, the first part of this monograph shows how Mr. Steiner wrote his film music. From the first viewing and the spotting session to the final exact timing of the cues, the whole creative and technical process of his film composing is demonstrated. The music of Max Steiner has a couple of quasi formulaic elements: the regular use of leitmotifs, quotations from his own music and the accurate synchronisation of screen action and music cues (with its extreme form, the so-called mickey mousing). The principles of the subjective use of harmonies as well as the technique of instrumentation are shown. The reader will also learn about the special relationship between composer and orchestrator. This distinctive form of collaboration was typical for the Hollywood cinema of the 30ies and 40ies of the 20th century, the so called Golden Age and still is today. Because the studios wanted to save the precious time of their employed composers, they wanted them to write their music on sketch paper with two to four staves, with the themes, voice leadings, harmonies and basic requirements of instrumentation. Then the orchestrator had to transform this into a complete score. Throughout his whole career, Mr. Steiner had been working with three orchestrators. This collaboration reached such an intuitive level, that is was sufficient that Max Steiner wrote only rudimentary musical information. When these sketches had been transformed into scores, Steiner conducted the studio orchestra, where he normally used the click. The second part of the book is based to a big extent on Steiner's yet unpublished autobiography. Born at the end of the 19th century in Vienna, Max Steiner was considered a musical wunderkind. His father as well as his grandfather before him was a famous theatre impresario. One of his teachers was Gustav Mahler. Steiner's first career as composer, arranger and conductor of operettas and musicals led him from Vienna to London and New York and lasted about 30 years. Then, in 1929, he got a call from Hollywood where he fulfilled his determination as dean of film music (Bette Davis). In the 50ies, when the symphonic film music lost its acceptance also Max Steiner's amount of work decreased. In 1965 he wrote his last of more than 300 scores. With the help of original documents from the archive of Warner Bros., such as memos, letters or billings the reader will get a three dimensional insight not only about how the movie Casablanca was made but on the mechanisms of the movie industry as a whole. Parts of the original sketches and the score of the music for Casablanca have been carefully transformed into a piano reduction to demonstrate even more clearly the efficient use of his skills and the yet highly artistic approach of Mr. Steiner Furthermore an example of this film music is compared to an excerpt of Richard Wagner's Ring des Nibelungen. There the reader will see how film music was not only inspired by but precisely obtained musical tools from the late romantic music theatre. Or, in Max Steiner's own words: "If Wagner would have lived in this century, he would be the number one film composer". Max Steiner is an outstanding protagonist of a generation of European immigrants who formed the cultural life in the USA. He is an important link between his native city Vienna and his new homeland America and through composers such as Steiner the tradition of the late European romantic m